1999
DOI: 10.1006/dbio.1999.9390
|View full text |Cite
|
Sign up to set email alerts
|

The Drosophila Jak Kinase Hopscotch Is Required for Multiple Developmental Processes in the Eye

Abstract: Jak kinases are critical signaling components in hematopoiesis. While a large number of studies have been conducted on the roles of Jak kinases in the hematopoietic cells, much less is known about the requirements for these tyrosine kinases in other tissues. We have used loss of function mutations in the Drosophila Jak kinase Hopscotch (Hop) to determine the role of Hop in eye development. We find that Hop is required for cell proliferation/survival in the eye imaginal disc, for the differentiation of photorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 55 publications
3
41
0
Order By: Relevance
“…Jak/Stat signaling directs a diverse spectrum of developmental events including cell migration, proliferation, patterning, and morphogenesis (reviewed in Arbouzova andZeidler 2006 andLi 2008). During eye development, the pathway promotes growth of the early eye field, contributes to initiation and movement of the morphogenetic furrow and to regional eye specification, transduces information from the dorsal-ventral axis to direct ommatidial rotation, and regulates specification and maintenance of the optic lobe neuroepithelium (Luo et al 1999;Zeidler et al 1999 Identification of hop, Stat92E, Socs36E, and Socs44A in our genetic screen ( Table 1) and finding that GMR-driven knockdown of these genes produces axon mistargeting phenotypes (Figure 2, A-E) suggested that the Jak/Stat pathway is also active in postmitotic photoreceptors. In support of this, expression of the 10xStat-eGFP pathway activity reporter suggests that early expression of the ligand, upd, which is absent by the third instar, enables sustained Jak/Stat signaling in the photoreceptors at the time they are sending out their axons (Bach et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Jak/Stat signaling directs a diverse spectrum of developmental events including cell migration, proliferation, patterning, and morphogenesis (reviewed in Arbouzova andZeidler 2006 andLi 2008). During eye development, the pathway promotes growth of the early eye field, contributes to initiation and movement of the morphogenetic furrow and to regional eye specification, transduces information from the dorsal-ventral axis to direct ommatidial rotation, and regulates specification and maintenance of the optic lobe neuroepithelium (Luo et al 1999;Zeidler et al 1999 Identification of hop, Stat92E, Socs36E, and Socs44A in our genetic screen ( Table 1) and finding that GMR-driven knockdown of these genes produces axon mistargeting phenotypes (Figure 2, A-E) suggested that the Jak/Stat pathway is also active in postmitotic photoreceptors. In support of this, expression of the 10xStat-eGFP pathway activity reporter suggests that early expression of the ligand, upd, which is absent by the third instar, enables sustained Jak/Stat signaling in the photoreceptors at the time they are sending out their axons (Bach et al 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Further increased expression of dpias or coupling with heterozygosity for the stat92E LOF allele stat 06346 led to transformation events with antennae frequently replacing eyes. LOF alleles of the Drosophila JAK-kinase hop of increasing severity cause the same sequence of increasing phenotypic abnormalities (17). Moreover, os 1 , a hypomorphic LOF allele of a JAK-STAT pathway ligand, results in small eyes (16, ʈ).…”
Section: Discussionmentioning
confidence: 99%
“…STAT92E then activates transcription, for example of the even skipped (eve) stripe 3 ϩ 7 enhancer (13,14). In addition to early lethality and segmentation phenotypes, LOF alleles of os and hop have uncovered widespread involvement of the pathway later in development, most well studied in eye ontogeny (17,18).…”
Section: A Drosophila Pias Homologue Negatively Regulates Stat92ementioning
confidence: 99%
“…All of these appear to represent regulatory alleles of the unpaired locus in which protein expression domains or levels are altered (Harrison et al, 1998). In addition to these upd alleles a number of weak loss-of-function alleles of hop have also been identi®ed (Perrimon and Mahowald, 1986;Luo et al, 1999). In di erent hetero-allelic combinations hop alleles can give rise to both small or no disc phenotypes as well as adult animals with held out wings and rough or disrupted eye phenotypes (Luo et al, 1999).…”
Section: Jak/stat Functions At Other Developmental Stagesmentioning
confidence: 99%
“…In addition to these upd alleles a number of weak loss-of-function alleles of hop have also been identi®ed (Perrimon and Mahowald, 1986;Luo et al, 1999). In di erent hetero-allelic combinations hop alleles can give rise to both small or no disc phenotypes as well as adult animals with held out wings and rough or disrupted eye phenotypes (Luo et al, 1999). Finally a weak stat92E allele, called stat92E hi-jak , has also been described and shows a range of adult phenotypes, including a subtle but clearly reproducible ectopic wing vein formation (Yan et al, 1996b).…”
Section: Jak/stat Functions At Other Developmental Stagesmentioning
confidence: 99%